Long-Term Outcomes of Distal Hypospadias Repair: A Patients’ Point Of View - Belgacem, Alexis; Fourcade, Laurent; Pelette, Romain; Bouchet, Etienne; Lescure, Victor; Bertherat, Walter; Spampinato, Grazia; Alain, Jean luc; Descazeaud, Aurélien; Ballouhey, Quentin (Urology Journal, 2020)
Purpose: To assess the long-term outcomes of patients treated for distal hypospadias. Assessment of long-term follow-up for a homogeneous population with hypospadias is difficult and there has consequently been a paucity of publications in this regard. Materials and Methods: A retrospective review was carried out to compile cases of distal hypospadias operated at our center between 1990 and 1999 according to the MAGPI procedure. Four parameters were evaluated based on four validated questionnaires: Health-related quality of life (SF-36), Genital self-perception (PPS), Self-esteem (Rosenberg Self-Esteem Scale), and Erectile function (IIEF). Results: A total of 77 patients who had undergone MAGPI surgery for hypospadias during the specified period were selected. Sufficient clinical data were available for 51 patients and only 15 of these patients were included, after a median follow-up of 22 years (20-26). Their outcomes were compared with those for a population of 15 matched circumcised men and 15 matched uncircumcised men. No significant difference was found between the patients and the control groups in terms of the score for quality of life (p = .29). There were, however, significant differences in the scores for self-perception of the penile cosmetic appearance (13.3 vs. 15.8; p < .01), self-esteem (30.6 vs. 35.8; p < .01), and erectile function (31.4 vs. 33.7; p = .04) between the patients and the controls. Lower self-esteem correlated with poor genital self-perception (r = .92). Conclusion: This study confirms that adult patients operated for distal hypospadias have poor genital self-perception. This poor genital perception correlated with lower self-esteem.